Graphitic Carbon Nitride/Nitrogen‐Rich Carbon Nanofibers: Highly Efficient Photocatalytic Hydrogen Evolution without Cocatalysts. Issue 36 (28th July 2016) - Han, Qing; Wang, Bing; Gao, Jian; Qu, Liangti
Abstract: An interconnected framework of mesoporous graphitic‐C3 N4 nanofibers merged with in situ incorporated nitrogen‐rich carbon has been prepared. The unique composition and structure of the nanofibers as well as strong coupling between the components endow them with efficient light‐harvesting properties, improved charged separation, and a multidimensional electron transport path that enhance the performance of hydrogen production. The as‐obtained catalyst exhibits an extremely high hydrogen‐evolution rate of 16885 μmol h −1 g −1, and a remarkable apparent quantum efficiency of 14.3 % at 420 nm without any cocatalysts, which is much higher than most reported g‐C3 N4 ‐based photocatalysts even in the presence of Pt‐based cocatalysts. Abstract : High in fiber : An interconnected framework of mesoporous graphitic‐C3 N4 nanofibers with in situ incorporated N‐rich carbon possesses a highly efficient photocatalytic activity for hydrogen evolution under visible light irradiation without cocatalysts. The activity is much higher than that of most previously reported g‐C3 N4 photocatalysts, even in the presence of Pt‐based cocatalysts.